2015
DOI: 10.1159/000381476
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Volume Estimations with Ellipsoid Equations by Magnetic Resonance Imaging in Autosomal Dominant Polycystic Kidney Disease

Abstract: Background: Kidney volume (KV) becomes clinically relevant in autosomal dominant polycystic kidney disease (ADPKD) management. KV can be conveniently estimated (ceKV) using ellipsoid volume equations with three axes measurements; however, the accuracy and reliability are unknown. Methods: KVs of 347 kidneys in 177 consecutive ADPKD patients were determined with a volumetric method (standard-KV), and ceKV was calculated using six different ellipsoid equations with three axes measurements using magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 24 publications
3
20
0
Order By: Relevance
“…The most commonly used methods for kidney volume computation such as manual delineation and stereology 13 are simple but time consuming and subject to intra/inter-observer variability. Alternatively, the mid-slice method 14 and the ellipsoid equation 15, 16 serve to provide quick TKV measurement but lead to low accuracy and precision compared to whole kidney segmentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used methods for kidney volume computation such as manual delineation and stereology 13 are simple but time consuming and subject to intra/inter-observer variability. Alternatively, the mid-slice method 14 and the ellipsoid equation 15, 16 serve to provide quick TKV measurement but lead to low accuracy and precision compared to whole kidney segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, several methods have been proposed with the goal of providing sufficiently accurate but less tedious means for TKV computation. The mid-slice method 14 and the ellipsoid volume equations 15, 16 have been proposed for estimating TKV from 1–2 slices. Even though these methods facilitate fast quantification, they provide only a rough estimate of TKV which could be convenient for clinical management but inadequate for clinical trials to detect smaller changes estimated to be approximately 5% 7, 10 per year.…”
Section: Introductionmentioning
confidence: 99%
“…1Ac, d) [17,36,38,39]. The 2 basic ellipsoid equations are as follows: The maximal width (W) is determined perpendicularly to L on the same slice that L is localized on.…”
Section: Ellipsoidal Formula For Ultrasound Mri or Ctmentioning
confidence: 99%
“…Higashihara et al [38] showed that intra-and interobserver reproducibility of kidney dimensions and calculated renal volumes derived from MRI scans was good, with an intraclass correlation coefficient of > 0.9. However, compared with standard planimetry, the ellipsoid formulas used tended to underestimate kidney volume, with the most accurate formula being π/24 × L × (W + WW) 2 .…”
Section: Ellipsoidal Formula For Ultrasound Mri or Ctmentioning
confidence: 99%
“…To evaluate the potential use of urinary parameters as a predictor of an increased TKV, the basic ellipsoid equation, which correlates strongly with the kidney volume measured by MRI, was used to estimate the TKV in 20-(n=12) and 24-week-old (n=12) rats as described below [14]: TKV = (maximal longitudinal length × maximal width × maximal depth × π/6) of the left kidney + (maximal longitudinal length × maximal width × maximal depth × π/6) of the right kidney…”
Section: Total Kidney Volume (Tkv)mentioning
confidence: 99%